With microbes - Ivana Suboticki (Nordic Journal of Science and Technology Studies, 2024)
With Microbes offers an analysis of the multiple, complex and dynamic relationships between humans and microbes and their entanglement in everyday life. Microbes have gained much attention from scientists, in popular culture, and by various actors looking to economize and regulate microbes, discussing questions such as the relationship  between gut microbes and brain activity, the best ways to nurture kombuchas and sourdough starters, or use and understanding of microbes as medicine. I was intrigued to read the book both due to my own interest in nurturing a good microbiome and wanting to review how one can approach the subject through an  innovative science and  technology studies (STS) approach.